Komunikasi Bencana Sebagai Sistem Mitigasi Bencana Hidrometeorologi Akibat Perubahan Iklim di Jakarta - Tresnanti, Desratri Timur; Kurniadi, Anwar; Puspito, Deffi Ayu; Widodo, Pujo; Kusuma, Kusuma (PendIPA Journal of Science Education, 2024)
This study highlights the crucial role of communication in managing hydrometeorological disasters in Jakarta, especially in addressing the impacts of climate change such as floods and heat waves. Effective communication, before, during, and after a disaster, has proven vital in reducing disaster risks and impacts. Data from BMKG and BPBD DKI Jakarta indicate that the increase in extreme rainfall and the poor city drainage system exacerbate flood events, while heat waves require specific communication strategies to protect the public from health risks. This study employs a literature review method, collecting data from various scientific literature to develop a comprehensive disaster management concept. The results show that mitigation, preparedness, response, and recovery approaches supported by targeted and inclusive communication can enhance community resilience. Initiatives such as socialization, preparedness simulations, and the use of social media are effective in disseminating information and improving community preparedness. BPBD DKI Jakarta's commitment to collaborating with various parties and utilizing the latest information technology underscores the importance of communication in modern disaster management. These efforts aim not only for short-term mitigation but also to build a more resilient community in facing future climate change challenges.